1994
DOI: 10.1111/j.1470-6431.1994.tb00682.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sensory evaluation of aromatic rice by consumers in East and South‐east Asia

Abstract: Quality of aromatic rice was compared by sensory evaluation with ordinary bland rice. Hieri, one of the varieties of aromatic rice planted in Japan was accepted by Indonesian people as well as the persons living in Japan, who are from South-east Asia.Basmati, which has a strong aroma, was nor accepted by Japanese people who have not eaten aromatic rice before. They have the same degree of preference for Jasmine rice as Hien. This research confinned that the quality of Hieri is good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…There have also been examples of reports on food textural preferences, with studies displaying no significant differences between cultures; namely, studies done by Jaeger et al (1998) on the preference patterns of mealiness between British and Danish consumers, and Murray et al (2000) on textural preference between consumers of European origin and of Chinese origin. Also, differences in cultural preferences have also been reported on taste preferences of aromatic rice (Hori et al 1994), fruit juice formulation (Abdullah 1995), snack chips (Ward et al 1998) and herbal drugs (Pieroni and Torry 2007), showing that cultural sensory variation is apparent and context dependant.…”
Section: Introductionmentioning
confidence: 99%
“…There have also been examples of reports on food textural preferences, with studies displaying no significant differences between cultures; namely, studies done by Jaeger et al (1998) on the preference patterns of mealiness between British and Danish consumers, and Murray et al (2000) on textural preference between consumers of European origin and of Chinese origin. Also, differences in cultural preferences have also been reported on taste preferences of aromatic rice (Hori et al 1994), fruit juice formulation (Abdullah 1995), snack chips (Ward et al 1998) and herbal drugs (Pieroni and Torry 2007), showing that cultural sensory variation is apparent and context dependant.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies reported no significant differences in textural preference between cultures. However, cultural differences have also been reported on taste preferences of fruit juice formulation (Abdullah 1995), aromatic rice (Hori et al. 1994), herbal drugs (Pieroni and Torry 2007) and snack chips (Ward et al.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies reported no significant differences in textural preference between cultures. However, cultural differences have also been reported on taste preferences of fruit juice formulation (Abdullah 1995), aromatic rice (Hori et al 1994), herbal drugs (Pieroni and Torry 2007) and snack chips (Ward et al 1998), reflecting that cultural sensory variation is still unclear, but is evident and context dependent. This discrepancy is believed to be contributed by factors such as consumer familiarity with and exposures to foods (Laing et al 1994;Prescott and Bell 1995;Prescott 1998), level of understanding of the sensory vocabulary and terms (Aström et al 2006) and individual differences (Rozin 1990a,b) arising from experience, dietary habits and attitudes to food (Rozin et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…When farmers become conscious of their rice quality, they are driven to produce better quality rice. Aromatic rice varieties are very popular in South and South East Asia and have recently gained wider acceptance in the USA, Europe and East Asia, especially in China 5,6 . Due to their characteristics such as aroma and flavor, they are highly favored, and command higher prices in markets.…”
Section: Introductionmentioning
confidence: 99%